Mining the multifunction of mucosal-associated invariant T cells in hematological malignancies and transplantation immunity: A promising hexagon soldier in immunomodulatory - Gao, Meng-Ge; Zhao, Xiao-Su (Frontiers in Immunology, 2022)
Mucosal-associated invariant T (MAIT) cells are evolutionarily conserved innate-like T cells capable of recognizing bacterial and fungal ligands derived from vitamin B biosynthesis. Under different stimulation conditions, MAIT cells can display different immune effector phenotypes, exerting immune regulation and anti-/protumor responses. Based on basic biological characteristics, including the enrichment of mucosal tissue, the secretion of mucosal repair protective factors (interleukin (IL)-17, etc.), and the activation of riboflavin metabolites by intestinal flora, MAIT cells may play an important role in the immune regulation effect of mucosal lesions or inflammation. At the same time, activated MAIT cells secrete granzyme B, perforin, interferon γ and other toxic cytokines, which can mediate antitumor effects. In addition, since a variety of haematological malignancies express the targets of MAIT cell-specific effector molecules, MAIT cells are also a potentially attractive target for cell therapy or immunotherapy for haematological malignancies. In this review, we will provide an overview of MAIT research related to blood system diseases and discuss the possible immunomodulatory or antitumor roles that unique biological characteristics or effector phenotypes may play in haematological diseases.